Household economic strengthening and the global fight against HIV. (25th July 2018) - Moret, Whitney; Carmichael, Jennine; Swann, Mandy; Namey, Emily
ABSTRACT: A range of economic interventions focused on vulnerable households and individuals – here collectively referred to as household economic strengthening (HES) – aim to address economic wellbeing and influence the economic determinants of HIV. Increasingly implemented as part of multi-sectoral programs, HES interventions have the potential to mitigate HIV-related risk behaviors and improve care and treatment outcomes. In order to engage donors, practitioners and researchers in a thoughtful discussion about where the field stands, the Accelerating Strategies for Practical Innovation and Research in Economic Strengthening (ASPIRES) project conducted an evidence review that comprehensively documents the literature linking a wide range of HES activities to HIV prevention and risk reduction as well as outcomes across the HIV care and treatment cascade. ASPIRES then held an expert consultation to reflect on the evidence review findings and define priorities for the field going forward. This article introduces this special issue of AIDS Care on HES for HIV Outcomes as an effort to expand and continue this discussion with a wider group of stakeholders. We present where the field stands, highlighting high level findings from the evidence review. Next, we present an overview of the expert consultation and resulting recommendations, highlighting concrete ways to strengthen the evidence base. Finally, we introduce the contents of this special issue and present insights on where the field is going.